THE EFFECTS OF PRODUCT QUALITY AND PROMOTION ON CUSTOMER PURCHASE INTENTION ON FOODS OFFERED THROUGH ONLINE DELIVERY SERVICES - Sudrajat, Deny; Wijayanti, Silvana Kardinar; Wibowo, Sandi Nasrudin; Fajarianto, Otto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
growing since then. All F & B retail businesses regardless the size are expected to seize the opportunity and maximize the benefit of partnering with this kind of service to better reach customers. Moreover, for MSMEs online platforms allow them to compete attract wider segment of customers. This study aims to determine the effects of product quality and promotion simultaneously and partially on customer purchase intention on foods offered through online food delivery services. Using quantitative approach, data collected by distributing questionnaire to 102 users of online delivery services in Tangerang city via social media. The results of this study revealed that simultaneously product quality and promotion have positive and significant effect on purchase intention. While partially product quality has a positive but no significant effect and promotion has positive and significant effect on purchase intention. This study suggests that MSMEs should know how to post or display pictures of their foods in attractive ways on food delivery application and utilize various promotional tools to increase customer purchase intention.